Social Service With Students At Ma Indistry Al-Jabar, Batam City - Pratama, Tito; Dailami, Dailami; Ilham, Wahyudi; Thandzir, Moh.; Yusuf, Abd Rahmad (PUSLITABMAS-Politeknik Pariwisata Batamc, 2025)
Social service is an activity carried out by individuals or groups with the aim of helping and providing benefits to communities in need. Typically, these activities are carried out voluntarily without expecting material rewards, but rather focusing on social and humanitarian concerns. Social service often includes activities such as: Distribution of staple goods (basic necessities) to underprivileged communities. Free medical treatment for those unable to afford healthcare costs. Education and training to enhance the skills of the community. Donations for disaster victims or communities in distress. Environmental clean-up or other activities aimed at improving the quality of life. The main goal of social service is to help alleviate the burdens of others, strengthen the bonds of brotherhood, and create a society that is more caring for one another. These activities are usually carried out by social institutions, community organizations, or youth groups with a spirit of mutual cooperation.